PENDEKATAN DAKWAH DALAM MEMBINA PENGAMALAN AGAMA INA-INA: (Studi Kasus Ina-Ina Pedagang Kaki Lima Pasar Inpres Kota Palu) - Nur Wahidah Alimuddin (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2017)
Da'wah is meant to nurture Muslims especially those who have long embraced Islam but have not implemented the teachings of Islam in accordance with the provisions set by the Islamic religion. Thus, da'wah in particular is striving for messages of da'wah to mad, u and live in life, so that created the benefit of life not only in the world but more important in the afterlife. However, the reality of mad'u is shifting in value, so it is far from their own religion. Many people are crushed by the economic consequences of helplessness, so they spend their time just to seek a worldly life. Conditions like this that happens in some